Vitamin D status in Bangladeshi subjects: a laboratory based study (BIRDEM Medical Journal, 2019)
Background: Vitamin D plays important role in normal functioning of multiple organs of the body. Hypovitaminosis D is known to be prevalent worldwide including the tropical countries. The present study was carried out to evaluate the vitamin D status in Bangladeshi patients undergoing laboratory investigation for vitamin D.Methods: This was a laboratory-based study. Data were extracted from the database of a diagnostic centre of Dhaka city and were analysed. Vitamin D status was defined as follows: deficiency 0 to